Living Well to Keep Your Pressure Down - Linda B. Bobroff (EDIS)
Revised! FCS-8690, a 6-page fact sheet by Linda B. Bobroff, describes risk factors for hypertension (high blood pressure) and lifestyle practices that help keep blood pressure within a healthy range. Includes additional sources of information. Published by the UF Department of Family Youth and Community Sciences, August 2008.